2020
DOI: 10.1021/acsomega.0c03357
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Behavior of a Silicide Electrode with Lithium in an Ionic-Liquid Electrolyte

Abstract: Silicides are attractive novel active materials for use in the negative-electrodes of next-generation lithium-ion batteries that use certain ionic-liquid electrolytes; however, the reaction mechanism of the above combination is yet to be clarified. Possible reactions at the silicide electrode are as follows: deposition and dissolution of Li metal on the electrode, lithiation and delithiation of Si, which would result from the phase separation of the silicide, and alloying and dealloying of the silicide with Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…, FeSi 2 + y Li + + y e − → Li y Si 2 + Fe and/or FeSi 2 + y Li + + y e − → Li y Si + FeSi) occurs and the silicide itself reacts with Li. 34…”
Section: Resultsunclassified
See 3 more Smart Citations
“…, FeSi 2 + y Li + + y e − → Li y Si 2 + Fe and/or FeSi 2 + y Li + + y e − → Li y Si + FeSi) occurs and the silicide itself reacts with Li. 34…”
Section: Resultsunclassified
“…It has been previously reported that the silicide phase does not separate into Si and metal and/or Si-poor silicide phases during charge-discharge processes; the reversible capacity is not obtained by lithiation and delithiation of the Si phase. 34 Fig. 7 and 8 demonstrated that the discharge capacity is not correlated with the amount of Si included in the silicide.…”
Section: Paper Materials Advancesmentioning
confidence: 93%
See 2 more Smart Citations
“…42 min). We did not limit the discharging time and set the cut-off voltage at 2.000 V. Herein, we ignored the capacity of LaSi 2 : silicide- and Si-alone electrodes react with Li, ,,, whereas silicide in the silicide/Si composite electrode should be electrochemically inactive in Li . The current density was set at 0.36 A g­( Si ) −1 (0.1 C ) and 1.44 A g­( Si ) −1 (0.4 C ) during the first cycle and subsequent cycles, respectively.…”
Section: Methodsmentioning
confidence: 99%